ELITE GUS CILIK DALAM PAGUYUBAN PADANG SAMBIAN BERSATU - Wahyuni, Ni Made Asri; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2019)
ABSTRACT The role of the Gus Cilik's Elite in the Padang Sambian Bersatu became interesting in this study by explaining the role of  Elite Gus Cilik and Padang Sambian Bersatu in  Pakraman Village of Padang Sambian. The theory used by the author owned Elite theory by Suzanne Keller. The method used in this research is descriptive qualitative, while data collection techniques are through observation, in-depth interviews and documentation. In this study concluded that Gus Cilik one of factor existence as a political elite will be the result of the support Paguyuban Sambian Bersatu is also influenced by his background as a traditional elite and local elite. Key words: Gus Cilik, Padang Sambian Bersatu, Suzanne Keller